Paraguay : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2009)
This paper discusses key findings of the detailed assessment report on antimoney laundering and combating the financing of terrorism (AML/CFT) for Paraguay. The assessment reveals that there are significant gaps in Paraguay's AML/CFT framework, and the level of awareness of money laundering/financing of terror risks is low in both the public and private sectors. The country falls well short of complying with most of the Financial Action Task Force recommendations. There are also no provisions that would allow the authorities to freeze suspected terrorist assets in accordance with the relevant UN Security Council Resolutions.